Nazwy karczem - historia karczemnictwa, charakter użytkowy na przestrzeni wieków, tendencje nazewnicze - Starzykiewicz, Agnieszka (Słowo. Studia językoznawcze, 2014)
The article concerns the issue of the evolution of the names of the inns and similar places. The first part of the article includes some information about the history of the taverns operation in Poland. There is also shown the change of the inns’ nature over the centuries. The second part of the article involves short characteristics of the research about the inns’ names and tries to show the primary naming trends. The aim of the article is the attempt to indicate the contemporary methods and naming processes, what allowed to put forward a thesis about the evolution of the names of the Polish inns.